Evaluation of the effect of nano-encapsulated Lippia origanoides essential oil extract on Salmonella serovar Enteritidis as a natural alternative to antibiotics in the poultry industry - Atencio-Vega, Abdiel; Bueno, Dante J.; Uribe-Diaz, Santiago; Maguey-Gonzalez, Jesus A.; Hernandez-Velasco, Xochitl; Martin, Kristen; Laverty, Lauren; Filho, Raphael L. A. [UNESP]; Señas-Cuesta, Roberto; Gray, Latasha S.; Marcon, Raul F. R.; Stein, Andressa; et al. (German Multidisciplinary Publishing Center, 2024)
The purpose of the present research was to evaluate the bactericidal activity of a formulation of thymol chemotype of Lippia origanoides essential oils (LOEOs) nano-encapsulated in maltodextrin against Salmonella ser. Enteritidis (SE) in an in vitro crop assay and in a prophylactic broiler chicken model using three low doses of the product: 75 ppm, 150 ppm, and 300 ppm. Two trials of each assay were conducted. Day-of-hatch male Cobb-Vantress broiler chickens were randomly allotted to one of four groups: G1) positive control group; G2) 75 ppm LOEOs group; G3) 150 ppm LOEOs group; G4) 300 ppm LOEOs group. Chicks were fed and watered ad libitum in heated brooder batteries in a controlled, age-appropriate environment. On day seven of age, all chickens were orally gavaged with 108 colony-forming units (CFU) of SE. Chickens were euthanized by exposure to CO2 for 24 hours after the SE challenge. Recovery of SE was evaluated in the liver, spleen, and ceca (including cecal tonsils). None of the three microencapsulated LOEOs doses changed SE concentration (p>0.05) in the in vitro crop assay. Similarly, no significant differences in SE were observed in the organ and intestinal colonization in broiler chicken trials. Therefore, the low concentrations of the nano-encapsulated LOEOs used do not reduce SE concentration in different poultry models. Further studies are needed to optimize the formulation, delivery, models, and concentration of essential oils to control Salmonella infections in broiler chickens effectively.
Keywords: Chickens; In vitro crop assay; Lippia origanoides; Salmonella ser. Enteritidis; Thymol chemotype